A Comparative Study of Mesoporous Silica and Mesoporous Bioactive Glass Nanoparticles as Non-Viral MicroRNA Vectors for Osteogenesis - Sepanta Hosseinpour; Maria Natividad Gomez-Cerezo; Yuxue Cao; Chang Lei; Huan Dai; Laurence J. Walsh; Saso Ivanovski; Chun Xu (MDPI AG, 2022)
Micro-ribonucleic acid (miRNA)-based therapies show advantages for bone regeneration but need efficient intracellular delivery methods. Inorganic nanoparticles such as mesoporous bioactive glass nanoparticles (MBGN) and mesoporous silica nanoparticles (MSN) have received growing interest in the intracellular delivery of nucleic acids. This study explores the capacity of MBGN and MSN for delivering miRNA to bone marrow mesenchymal stem cells (BMSC) for bone regenerative purposes, with a focus on comparing the two in terms of cell viability, transfection efficiency, and osteogenic actions. Spherical MBGN and MSN with a particle size of ~200 nm and small-sized mesopores were prepared using the sol-gel method, and then the surface was modified with polyethyleneimine for miRNA loading and delivery. The results showed miRNA can be loaded into both nanoparticles within 2 h and was released sustainedly for up to 3 days. Confocal laser scanning microscopy and flow cytometry analysis indicated a high transfection efficiency (>64%) of both nanoparticles without statistical difference. Compared with MSN, MBGN showed stronger activation of alkaline phosphatase and activation of osteocalcin genes. This translated to a greater osteogenic effect of MBGN on BMSC, with Alizarin red staining showing greater mineralization compared with the MSN group. These findings show the potential for MBGN to be used in bone tissue engineering.